The Ability of an Algoclay-Based Mycotoxin Decontaminant to Decrease the Serum Levels of Zearalenone and Its Metabolites in Lactating Sows - Benthem de Grave, Xandra; Saltzmann, Janine; Laurain, Julia; Rodriguez, Maria A.; Molist, Francesc; Dänicke, Sven; Santos, Regiane R. (Frontiers in Veterinary Science, 2021)
This study evaluated the effect of an algoclay-based mycotoxin decontaminant on the levels of ZEN, DON, and their derivatives in the colostrum, milk, and serum of sows, as well as in the serum of weaned piglets after maternal mycotoxin exposure during the last week of gestation and during lactation of sows (26 days). For this, sows (n = 5) were fed diets artificially contaminated with 100 (LoZEN) or 300 (HiZEN) ppb ZEN, with or without an algoclay-based mycotoxin decontaminant in the highly contaminated diet. All diets contained 250 ppb deoxynivalenol (DON). Dietary treatments did not affect the performance of the sows and piglets. Only α-ZEL was significantly increased in the colostrum of sows fed the HiZEN diet, and this increase was even higher in the colostrum of the sows fed the HiZEN diet supplemented with the test decontaminant. However, no differences in milk mycotoxin levels were observed at weaning. The highest levels of ZEN, α-ZEL, and β-ZEL were observed in the serum of sows fed the HiZEN diet. When the HiZEN diet was supplemented with the tested algoclay-based mycotoxin decontaminant the levels of ZEN and its metabolites were significantly decreased in the serum of sows. Although all sows were fed the same levels of DON, the serum level of de-epoxy-DON was increased only in the serum of piglets from the sows fed a diet with the non-supplemented HiZEN diet. In conclusion, the tested algoclay-based mycotoxin decontaminant can decrease the levels of ZEN and its metabolites in the serum of sows and the level of de-DON in the serum of piglets.